Teclo, logo existo: uma análise das formas de sociabilidade em redes sociais construídas a partir das telenovelas - Gleison Barreto Salin (2014)
Two important habits provided the basis for this research. The Rirst one is TV viewing. The second - which is becoming more and more characteristic of brazilians - is the use of social networks on the internet. So common, the TV viewing habits and commenting on what you see on social networks, have also grown widely in recent years. The convergence of media may change the forms of sociability, allowing viewers to take ownership of a new space for discussion. This research analyzed the sociability that arises online from these TV content, looking for changes in the relationship between producers and consumers when they are interacting in the same interactional space.